Production views and scientific collaboration networks. Indicators and comparatives. South America and other countries (2022)
Objective: To carry out a comparative analysis of scientific production between South America and other latitudes. The study and analysis of variables related to production based on cartograms, number of researchers per million inhabitants, investment resources in ST&I and collaboration networks, among others, is provided.  Originality/contribution: The production of scientific knowledge has become an important factor in countries and higher education institutions, being associated as an indicator of development, with principles demanded by quality accreditation agencies. Method: It is approached under a descriptive quantitative structure, with the help of relational indicators. Strategies/information collection: Collection of information through cartograms in order to determine the trend of gaps from mapping densities, showing a remarkable growth in Asian countries. Colombia, when compared to countries in South and Central America, shows production indicators below Brazil, Argentina and Mexico, with less human resources and investment; however, when calculating values relative to its context, the picture changes substantially. Conclusions: In relation to collaboration networks, motivated by the pandemic crisis, we conclude an increase in international participation through co-authorships of scientific articles in the health sector, with an average of approximately 50%. It should be noted that most of this research was carried out in institutions of higher education.